Enantioselective Conjugate Allylation of Cyclic Enones - Taber, Douglass F. (2011)
[Image: see text] Enantioselective organocatalytic 1,2-allylation of a cyclic enone followed by anionic oxy-Cope rearrangement delivered the ketone as a mixture of diastereomers. This appears to be a general method for the net enantioselective conjugate allylation of cyclic enones.